Spoken Correction for Chinese Text Entry - Hsu, Bo-June (Paul); Glass, James (International Symposium on Chinese Spoken Language Processing (ISCSLP), 2006)
With an average of 17 Chinese characters per phonetic syllable, correcting conversion errors with current phonetic input method editors (IMEs) is often painstaking and time consuming. We explore the application of spoken character description as a correction interface for Chinese text entry, in part motivated by the common practice of describing Chinese characters in names for self-introductions. In this work, we analyze typical character descriptions, extend a commercial IME with a spoken correction interface, and evaluate the resulting system in a user study. Preliminary results suggest that although correcting IME conversion errors with spoken character descriptions may not be more effective than traditional techniques for everyone, nearly all users see the potential benefit of such a system and would recommend it to friends.